Cerebral Dominance for Language in Literates and Illiterates: A Study With Normals - Kumar PJ (Journal of All India Institute of Speech and Hearing, 1970)
Thirty  normal  right  handed  literate   and  thirty  normal  right  handed illiterate  adults  were  administered with a dichotic verbal recall task to determine cerebral dominance for  language  and to see whether there was any difference in cerebral dominance for language  in between these groups. The results  indicated a statistically  significant  difference in cerebral dominance for  language for literate and illiterate adults. 13.42 percent of  the illiterate subjects and 90 percent of literate subjects showed a left hemisphere dominance for language. Bilateral representation for language was observed in 43.29  percent of illiterates  and 10 percent  of literates. Right hemisphere dominance for language was observed with 43.29  per cent of the illiterates and it was not exhibited by  any of the  30 literate subjects.